Experimental Characterization of Hybrid Ventilation Systems in Residential Buildings - Pinto, Manuel (2005)
In the recent past, residential buildings in temperate climates were ventilated by the daily opening of windows and by exaggerated window and door permeability. Energy conservation concerns have led to better quality windows and lower air permeability that consequently increased the risk of condensation whilst decreasing indoor air quality. Because of the variation in natural factors, such as wind speed and the stack effect, natural ventilation systems are unlikely to permanently provide ideal ventilation rates. As such, we will characterize the performance of hybrid ventilation systems (air intake through automatically regulated louvers in bedrooms and living rooms, natural exhaust in bathrooms and fan exhaust systems in kitchens) that are a possible solution to this drawback. In March of 2002 and January of 2003, we measured air change rates in a 2-bedroom apartment using the PFT technique. This method has the advantage of measuring air renewal rates in inhabited apartments during a reasonable period and thereby reveals air renewal rates in the dwelling and also in each compartment. This article will demonstrate the results obtained at a standard apartment and will present the experimental study characterising the hybrid ventilation system in a 100-apartment residential complex in the Porto area. The study evaluates the façade’s permeability and the respective air exchange rates per compartment using the PFT and the constant concentration techniques.